Formal and informal metalanguage in primary teachers’ talk about informational student texts - Jenny W. Folkeryd; Åsa af Geijerstam (Nordic Journal of Literacy Research, 2019)
Previous research has pointed out the importance for teachers as well as students to use metalanguage in order to develop writing in school. Few studies have however focused on how teachers talk about content aspects in young students’ informational texts, using formal (technical) as well as informal (non-technical) metalanguage. The main purpose of the present study is therefore to analyze how primary teachers discuss student texts before and after a series of six professional development workshops. Based on research within a social semiotic perspective, the workshops focused linguistic resources to express and develop ideas, create cohesive texts and interact with an audience. During audio recorded discussions, a group of teachers were asked to comment on strengths and weaknesses in two informational texts written by students in grades 2 and 3. In order to investigate the effect of the subsequent training, the same texts were discussed during the first and the last meeting. The analysis shows no difference in the total number of metalinguistic comments before and after the workshops. However, explicit formal metalanguage replaces informal metalanguage to a significant degree. It is also shown that the informal metalanguage to some extent displayed other affordances than the formal metalanguage.